2019
DOI: 10.9734/jpri/2019/v29i330237
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Competencies of Community Pharmacists for Differentiated HIV Care and Services in Jos, Nigeria

Abstract: Background: Knowledge and competence of community pharmacists in HIV care, are essential for translating the goals of differentiated care into improved outcomes. Aims: To assess the knowledge and competence of community pharmacists in Jos, for differentiated HIV care and services. Study Design: Cross-sectional questionnaire survey. Place and Duration of Study: Community pharmacies in Jos North and Jos South local government areas of Plateau state, North-Central Nigeria, between September to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The result of this study showed that the average Likert scale value for respondents' perception towards community pharmacists' involvement in management of HIV infected patients was biased towards agreement, 3.89 (approximately 4). This finding agreed with previous studies 19,20 , where majority of community pharmacists showed positive disposition to use their practice site, and willingness to extend access for differentiated HIV care 21 . The result further confirmed the research reports that evaluated views of pharmacists and other stakeholders regarding integration of community pharmacies into primary care pathway 22 .…”
Section: Perception Of Community Pharmacists Towards Management Of Hisupporting
confidence: 92%
“…The result of this study showed that the average Likert scale value for respondents' perception towards community pharmacists' involvement in management of HIV infected patients was biased towards agreement, 3.89 (approximately 4). This finding agreed with previous studies 19,20 , where majority of community pharmacists showed positive disposition to use their practice site, and willingness to extend access for differentiated HIV care 21 . The result further confirmed the research reports that evaluated views of pharmacists and other stakeholders regarding integration of community pharmacies into primary care pathway 22 .…”
Section: Perception Of Community Pharmacists Towards Management Of Hisupporting
confidence: 92%
“…Similarly, community pharmacists in Jos, Nigeria, reported low knowledge and weak competency in HIV care emphasizing the need for specialized training before the implementation of differentiated care model. 43 Community pharmacist respondents based on demographic characteristics showed that sex and qualifications of the respondents do not have effect on their involvement in HIV/AIDS services. This is in line with the study conducted among community pharmacists in southeast Nigeria.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, community pharmacists in Jos, Nigeria, reported low knowledge and weak competency in HIV care emphasizing the need for specialized training before the implementation of differentiated care model. 43…”
Section: Discussionmentioning
confidence: 99%
“…The final questionnaire consisted of four sections: Demographic characteristics of respondents, Competencies of community pharmacists for HIV care and services, Views and attitudes of community pharmacists regarding differentiated HIV care and services, Community pharmacists' knowledge of HIV pharmacotherapy. The sections on knowledge and competencies have been reported elsewhere along with details of the methods for the wider study for which this was a part [16]. The portion of the study reported in this paper consisted of 10 questions on a Likert scale, to assess attitudes and perceptions of community pharmacists on differentiated HIV care and services.…”
Section: Methodsmentioning
confidence: 99%
“…Methods: This was a cross-sectional survey of community pharmacists in Jos, Plateau state, Nigeria. The portion of the study reported in this paper consisted of a 10 items Likert questions to assess attitudes and perceptions of community pharmacists on differentiated HIV care and Dapar et al; ISRR, 8(2): 1-10, 2019; Article no.ISRR.51502 2 services. The Statistical Package for Social Sciences version 20 was used to manage data.…”
mentioning
confidence: 99%